Influence of feed processing on the performance, nutrient utilisation and gut development of poultry and feed quality : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Poultry Nutrition at Massey University, Palmerston North, New Zealand - Abdollahi, Mohammad Reza; Abdollahi, Mohammad Reza (Massey University, 2011)
The first two experiments of this thesis investigated the effects of conditioning temperature in relation to grain type (maize, wheat and sorghum) on the performance, nutrient utilisation and digestive tract development of broiler starters. The third experiment examined the influence of feed form (mash vs. pellet) and conditioning temperature in broiler starters fed wheat-based diets. The effects of improved pellet quality from the addition of a pellet binder or/and moisture to a wheat-based diet, and the effects of pellet diameter and pellet length on the quality of pellets and, performance, nutrient utilisation and digestive tract development of broilers were studied in fourth and fifth experiments, respectively. In the first experiment discussed in Chapter 4, increasing conditioning temperatures decreased the weight gain and feed intake of broilers fed wheat-based diets, whereas birds fed maize-based diets conditioned at 60 and 90 ºC had higher weight gain and feed intake than those fed the diet conditioned at 75 ºC. Increasing conditioning temperatures increased the feed per gain in both grain-type diets. Pellet durability index (PDI) improved with increasing conditioning temperatures in wheat-based diets, but was unaffected in maize-based diets. In wheat-based diets, increasing conditioning temperatures decreased the ileal digestibility of nitrogen (N) and starch. Ileal N digestibility of maize-based diets conditioned at 60 and 90 ºC was higher than at 75 ºC. Starch digestibility was unaffected by conditioning temperature in maize-based diets. No effect of conditioning temperature was found for the apparent metabolisable energy (AME). Data reported in Chapter 5 showed that birds fed maize- and sorghum-based diets conditioned at 60 ºC had a similar weight gain to those fed diets conditioned at 90 ºC and higher than those fed diets conditioned at 75 ºC. In both grain-type diets, birds fed diets conditioned at 60 and 90 ºC tended to have higher feed intake than those fed diets conditioned at 75 ºC. Conditioning temperature had no effect on the feed per gain. Increasing conditioning temperatures caused gradual improvements in the PDI of maize-based diets, while the improvement was marked in the sorghum-based diet conditioned at 90 ºC. In both grain-type diets, pellet hardness increased with increasing conditioning temperatures, particularly at 90 ºC. In maize-based diets, ileal N digestibility was poorer at 75 ºC compared with 60 and 90 ºC whereas ileal starch digestibility was unaffected by conditioning temperature and AME was higher at 75 ºC compared with 60 and 90 ºC. For sorghum-based diets, increasing conditioning temperatures resulted in linear reductions in the ileal N and starch digestibility and AME. Data reported in Chapter 6 showed that in mash diets, increasing conditioning temperatures above 60 ºC had negative effects on weight gain, feed per gain and nutrient utilisation of broiler starters. But the deterioration in performance parameters caused by conditioning at higher temperatures was restored when steam-conditioned mash diets were pelleted. Pellet durability and hardness increased with increasing conditioning temperatures. Data reported in Chapter 7 showed that the negative effect of higher conditioning temperature on weight gain, and to some extent feed intake, of broilers is not limited to the starter period (d 1 to 21), but can also be carried over the whole growth period (d 1 to 35). This study also illustrated possibilities for high quality pellets to be manufactured by the addition of pellet binder or/and moisture to a mash diet without the need for high conditioning temperatures. The final experiment (Chapter 8) demonstrated that increasing the pellet length from 3- to 6-mm during the grower period (d 10 to 21) positively influenced the weight gain and feed per gain of broilers. While the weight gain response disappeared as the birds grew older, improvements in feed per gain was maintained over the finisher (d 22 to 42) and whole grow-out (d 10 to 42) periods in 4.76-mm diameter pellets. This study also showed that using a small diameter die hole and longer pellet length may have an additive effect on pellet quality, and provide opportunities to produce high quality pellets under low conditioning temperatures. The major finding of this thesis research was that the balance between the negative effect of high conditioning temperatures on nutrient availability and the positive effect on pellet quality is relevant in determining the broiler performance. The probability and magnitude of these two counteracting effects determine the performance of broilers. Another important finding was that the pre-conditioning addition of moisture and the use of small diameter die hole and longer pellet length can effectively address pellet quality concerns at low conditioning temperatures.
Keywords: Broilers; Poultry feed; Poultry nutrition; Digestive tract development